2005
DOI: 10.1111/j.1365-2486.2005.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Do dams and levees impact nitrogen cycling? Simulating the effects of flood alterations on floodplain denitrification

Abstract: A fundamental challenge in understanding the global nitrogen cycle is the quantification of denitrification on large heterogeneous landscapes. Because floodplains are important sites for denitrification and nitrogen retention, we developed a generalized floodplain biogeochemical model to determine whether dams and flood-control levees affect floodplain denitrification by altering floodplain inundation. We combined a statistical model of floodplain topography with a model of hydrology and nitrogen biogeochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 88 publications
2
42
0
Order By: Relevance
“…However, neither of these approaches considers buffer zone shape, which can be important for increasing buffer zone effectiveness (e.g. Gergel et al 2005).…”
Section: Size and Shapementioning
confidence: 99%
“…However, neither of these approaches considers buffer zone shape, which can be important for increasing buffer zone effectiveness (e.g. Gergel et al 2005).…”
Section: Size and Shapementioning
confidence: 99%
“…Floodplains are frequently identified as important sites for nutrient retention and removal (Brinson et al 1984;Craft and Casey 2000;Gergel et al 2005;Forshay and Stanley 2005;Noe and Hupp 2009). Denitrification in particular has the potential to remove significant amounts of nitrogen (N) from floodplains, as seasonal river inundation establishes anaerobic soil conditions, delivers nitrate, and preserves carbon (C).…”
Section: Introductionmentioning
confidence: 99%
“…Models of the effects on nutrient reduction to the Gulf of Mexico were created (Galat et al, 1998;Lane et al, 2003;Mitsch et al, 2009;Opperman et al, 2009). Gergel et al (2005) modeled different hydrologic scenarios including lakes and leveed rivers as well as natural floodplains. They found that short, frequent floods processed more NO 3 than long infrequent floods.…”
Section: Introductionmentioning
confidence: 99%